Project-based learning not just for STEM anymore. (September 2016) - Duke, Nell K.; Halvorsen, Anne-Lise; Strachan, Stephanie L.
The popularity of project-based learning has been driven in part by a growing number of STEM schools and programs. But STEM subjects are not the only fertile ground for project-based learning (PBL). Social studies and literacy content, too, can be adapted into PBL units to benefit teaching and learning, the authors argue. They review key studies on PBL in social studies and literacy education, two examples of successful social studies/literacy PBL units, and conclude with tips for developing social studies and literacy projects in classrooms.